2023
DOI: 10.3390/microorganisms11061376
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Serotype Evolution and Burden in European Adults in the Last Decade: A Systematic Review

Abstract: Pneumococcal disease is a major cause of morbidity/mortality worldwide, and vaccination is an important measure in its prevention. Despite European children being vaccinated with pneumococcal conjugate vaccines (PCVs), pneumococcal infections are still a major cause of morbidity/mortality in adults with risk conditions and their vaccination might be an important prevention strategy. New PCVs have been approved, but information is lacking on their potential impact in European adults. In our review, we searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 94 publications
0
0
0
Order By: Relevance
“…Serotype 11A was the most prevalent serotype during the study period, more commonly associated with non-IPD cases in the elderly. In recent years, serotype 11A is a prevalent serotype in Europe, accounting for 2 - 7% IPD and 9 - 10% non-IPD [ 20 ]. Several studies have shown that 11A has low invasive potential, and is associated with antibiotic non-susceptibility and increased risk of death [ 21 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotype 11A was the most prevalent serotype during the study period, more commonly associated with non-IPD cases in the elderly. In recent years, serotype 11A is a prevalent serotype in Europe, accounting for 2 - 7% IPD and 9 - 10% non-IPD [ 20 ]. Several studies have shown that 11A has low invasive potential, and is associated with antibiotic non-susceptibility and increased risk of death [ 21 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a significant increase in penicillin resistance was also observed from 1.9% over the period 2017 - 2019 to 20.3% over the years 2020 - 2022. The increasing rates in PNSP was in part due to increases in pneumococcal diseases caused by serotypes not included in PCV13, and the persistence of serotype 19A [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries, some of these serotypes have been shown to cause more severe clinical manifestations such as meningitis [ 64 ]. In Europe, a systematic review found that these seven serotypes have an increasing trend in IPD incidence prevalence in adults [ 65 ]. PCV20 covers serotype 8, 10A, 11A, 12F, 15B, 22F, and 33F was licensed for adults >18 years in 2021 ( Fig.…”
Section: Pneumococcal Vaccine Developmentmentioning
confidence: 99%
“…According to the Global Burden of Disease Study, pneumococcal pneumonia was responsible for 1.5 million deaths in 2015, where 55.4% of all deaths were caused by lower respiratory tract infections [2]. Pneumococcal diseases are classified into two main categories: invasive pneumococcal disease (IPD) and noninvasive pneumococcal disease (NIPD) [3,4]. IPD is diagnosed when the bacterium is typically identified in sterile bodily fluids, leading to severe infections such as meningitis, sepsis, or bacteremic pneumonia [3,5].…”
Section: Introduction 1motivation and Backgroundmentioning
confidence: 99%
“…IPD incidence is impacted by various factors, including vaccination coverage, geographical location, underlying health conditions, smoking, and age [7]. Young children, infants, immunocompromised individuals, and the elderly bear the highest disease burden, both in developed and less developed countries [4,[7][8][9]. Specifically, children under 5 years old and elderly individuals aged 65 and above are particularly susceptible to developing pneumococcal disease [10].…”
Section: Introduction 1motivation and Backgroundmentioning
confidence: 99%